Relationship Between Knowledge, Attitude and Supervision Hand Hygiene Compliance - Tien, Wartini; Komariah, Maria; Nurhakim, Furkon (Poltekkes Kemenkes Palu, 2024)
Health Care Associated Infection has become a serious problem in hospitals, and one of the causes is low hand hygiene compliance. Factors influencing compliance with the five moments of hand hygiene are knowledge, attitudes, and supervision. Research was conducted to identify factors related to nurses' compliance with the implementation of the five moments of hand hygiene. Analytical correlational research with a cross-sectional approach was conducted at RSUD in November 2023 with a sample of 123 nurses. The questionnaire used was based on Herzbergh's motivation theory and the 26-item Manchester Clinical Supervision Scale (MCSS-26). Bivariate test using Chi Square, and multivariate analysis with logistic regression were performed. The results showed that there is a relationship between knowledge and compliance (p=0.000), there is a relationship between training and compliance (p=0.016). There is a relationship between motivation and compliance (p=0.000), there is a relationship between attitudes and compliance (p=0.000). There is a relationship between facilities and compliance (p=0.011), there is a relationship between supervision and compliance (p=0.000). The dominant factors influencing are supervision (3.178), attitude (2.921), and knowledge (0.138). The conclusion of the study is that there is a relationship between knowledge, training, attitudes, motivation, facilities, and supervision on compliance with the five moments of hand hygiene, the dominant factors influencing are supervision, attitude, and knowledge in order.